Profile of an occupation - textile production mechanic - Schambeck, Arne [Verfasser] (My University, 2020)
"In the spring of 2020, nearly one in two companies in the German textile and fashion industry became involved in helping to fill the gap in the supply of protective face coverings. By the end of April, production output had already reached 22 million masks a week and was still rising. One textile occupation is particularly crucial to the manufacture of the non-woven material that is required to make the masks - the textile production mechanic." (author's abstract; BIBB-Doku)
Keywords: S 6.2.2 Holzbearbeitung, Flechtwaren, Textil-, Leder- und Fellverarbeitung; Produktionsmechaniker - Textil; Tätigkeitsmerkmal